Insights into the neurochemical signature of the Innervation of Beige Fat - Aneta Stefanidis; Nicole M. Wiedmann; Sonika Tyagi; Andrew M. Allen; Matthew J. Watt; Brian J. Oldfield (Elsevier, 2018)
Objective: The potential for brown adipose tissue (BAT) to be targeted as a therapeutic option to combat obesity has been heightened by the discovery of a brown-like form of inducible "beige" adipose tissue in white fat which has overlapping structural and functional properties to "classical" BAT. The likelihood that both beige and brown fat are recruited functionally by neural mechanisms, taken together with the lack of a detailed understanding of the nature of changes in the nervous system when white adipose tissue (WAT) is transformed to brown, provides the impetus for this study. Here, we aim to identify whether there is a shift in the gene expression profile in neurons directly innervating inguinal white adipose tissue (iWAT) that has undergone "beiging" to a signature that is more similar to neurons projecting to BAT. Methods: Two groups of rats, one housed at thermoneutrality (27 °C) and the other exposed to cold (8 °C) for 7 days, were killed, and their T13/L1 ganglia, stellate ganglion (T1/T2), or superior cervical ganglion (SCG, C2/3) removed. This approach yielded ganglia containing neurons that innervate either beiged white fat (8 °C for 7 days), inguinal WAT (27 °C for 7 days), BAT (both 27 °C and 8 °C for 7 days) or non-WAT (8 °C for 7 days), the latter included to isolate changes in gene expression that were more aligned with a response to cold exposure than the transformation of white to beige adipocytes. Bioinformatics analyses of RNA sequencing data was performed followed by Ingenuity Pathway Analysis (IPA) to determine differential gene expression and recruitment of biosynthetic pathways. Results: When iWAT is "beiged" there is a significant shift in the gene expression profile of neurons in sympathetic ganglia (T13/L1) innervating this depot toward a gene neurochemical signature that is similar to the stellate ganglion projecting to BAT. Bioinformatics analyses of "beiging" related genes revealed upregulation of genes encoding neuropeptides proopiomelanocortin (POMC) and calcitonin-gene related peptide (CGRP) within ganglionic neurons. Treatment of differentiated 3T3L1 adipocytes with αMSH, one of the products cleaved from POMC, results in an elevation in lipolysis and the beiging of these cells as indicated by changes in gene expression markers of browning (Ucp1 and Ppargc1a). Conclusion: These data indicate that, coincident with beiging, there is a shift toward a "brown-like" neurochemical signature of postganglionic neurons projecting to inguinal white fat, an increased expression of POMC, and, consistent with a causative role for this prohormone in beiging, an αMSH-mediated increase in beige gene markers in isolated adipocytes. Keywords: Beige fat, RNA sequencing, Brown adipose tissue, Thermogenesis